Information management system for Pablo Galleries Online Repository - Domingo, Maria Johanna Caldito (Technology Management Center, 2013)
Technological developments in information technology and the internet have reshaped business models, and the way organizations run their business. Information has become a complex aspect in business environments and organizations are challenged with aligning information management and technology with their current business strategies to address future needs and developments of their company. "Traditional IT is changing and increasingly developing into information management and business process management. Safeguarding and managing information in an organization is no longer the exclusive responsibility of the technicians but one shared by everyone who has access to it. Information Management for any industry has become a significant factor for providing value to organizations, enabling their growth and development. We are in a generation in which knowledge and information has become significant factors in successful business environments. Information is the basis of all management decisions and strategies therefore; developing an information management strategy must be incorporated in the management planning of organizations. Information is a collection of the things we know that have a contextual meaning. Organizations must understand the relationships of these collections in order to transform them into knowledge that will create a business value for them. Developments in the World Wide Web and information management systems have been providing economic benefits in which many industries have already profited. The art industry has begun to explore the opportunities of these technological advancements and reinvent the realms of art galleries and museums. They have begun to use the World Wide Web to tap a larger market, distribute their collections for commercial exchange, and promote their art collections. Several digital asset management softwares have surfaced to manage the digital art collections of these commercial art exhibition space. This has enabled the users to search, access, retrieve and archive data effectively and efficiently. Art organizations need to leverage on these developments to help them strengthen their efforts in improving their business operations, and upholding their advocacies in the art industry. Julien Anfruns, Director General at the International Council of Museums (ICOM) has mentioned that "museums must compete to have an audible voice against a noisy background of new information, accelerating technology and an unstable climate, communicated by burgeoning social media. The IMD theme is a base from which to explore responses to change, an opportunity for museums of all kinds to showcase their best achievements and latest innovations. This will allow the art industry to reach a wider market, uphold education, preserve art collections, and encourage online discussions about art and its history. An extensive access for public use will make it possible for museums to realize their goals and objectives. The aim of these World Wide Web museums does not intend to replace physical building space for exhibiting art. The purpose of these cyberspace galleries is to supplement and support the main objectives of the actual galleries. Digital technology has been providing numerous new media opportunities within the art industry but the foundations of its success are still dependent on the physical museums as they are the ones that are in actual possession of artworks that provides value to the organization. The project proposal for Pablo Galleries is an Information Management System that will serve as a preliminary step in integrating art digitalization concepts within Pablo Galleries' business operations. This project is divided into three sections : (1) Business Analysis; (2) Project Development; and (3) Management and Maintenance Manual of the Information Management System. A business analysis activity was conducted to determine Pablo Galleries company background, current business operations and other practices. A needs assessment study was performed in order to identify gaps within their business operations. Owners of the gallery were provided with a quick business assessment form (created by CCFLI) to be able to identify which departments have weak services and other problems within the gallery's operations. The business analysis includes recommendations and business solutions that will help the gallery improved their overall business performance. The second phase of the project is the actual development of an Information Management System (IMS), a solution to the documentation problems of Pablo Galleries. This section details the preliminary steps and other prerequisites for developing an online repository. This phase presents the development of project templates that will be utilized to gather complete information about artworks and classify them according to specific categories. It aims to provide a comprehensive and standard format for gathering data and information. This will assure that all artworks to be digitalized and born-digital artworks will have a complete and informative context including administrative data that will be used in managing, and maintaining information about the artworks. The project development also includes a catalogue code system that will serve as a unique object identifier for each digital artwork that will allow users to search retrieve, access and archive information easily. A unique alphanumeric code will be assigned to each digital resource. The numeric and alphabetic composition of a catalogue code represents descriptive information about a specific art work such as art movement, art medium and artist. The catalogue code will also include an accession number, and the month & year the artwork was exhibited in Pablo Galleries. This system will enable users to navigate through the system, search and access information effectively and efficiently. The project templates and the catalogue code system are tools that will help the gallery plan and develop their online repository. The project will include a management and maintenance manual that details how the gallery can avoid the pitfalls of technology obsolescence and minimize the impacts of technology damage and deterioration. Digitalized artworks require continuous validatio and upgrades in order to maintain the quality and integrity of the collection. This paper details a maintenance strategy that will address issues on system upgrades, back-up data and if necessary, moving to new technology platforms. The aim is for Pablo Galleries to incur minimal cost on necessary changes, regular maintenance, and future upgrades. Running the over-all operations of the Information Management System and maintenance manual after the full implementation of the proposed project.